Genomic analysis of a cypovirus isolated from the eucalyptus brown looper, Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) - Horta, André Ballerini [UNESP]; Ardisson-Araujo, Daniel Mendes Pereira; da Silva, Leonardo Assis; de Melo, Fernando Lucas; da Silva Morgado, Fabricio; Franco Lemos, Manoel Victor [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Boiça, Arlindo Leal [UNESP]; Wilcken, Carlos Frederico [UNESP]; Ribeiro, Bergmann Morais (Elsevier, 2018)
The eucalyptus brown looper, Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae), is the main lepidopteran defoliator of eucalyptus plantations in Brazil. Outbreaks of this insect pest are common in Brazil and can affect the productivity of planted forests severely. T. arnobia caterpillars from a laboratory colony with viral infection symptoms were analyzed by electron microscopy that revealed polyhedral occlusion bodies (OBs) with several icosahedral virus particles embedded. Analysis of its genetic material showed ten segments of dsRNA, which confirmed this virus as a possible member of the genus Cypovirus. Phylogenetic analysis of the whole genome sequence revealed its close relationship with other isolates of Cypovirus 14 species and according to these results we proposed the name Thyrinteina arnobia cypovirus 14 (TharCPV-14) for this new virus isolate. Further research will be necessary in order to analyze the potential of this virus as a biopesticide.
Keywords: Biological control; Cypovirus; Eucalyptus; Forest protection; Thyrinteina arnobia